Surviving universities’ brand image in pandemic situation of Corona Virus: Role of ICT orientation and student satisfaction in Pakistan - Shehzadi, Sidra; Mustaffa, Che Su; Cheah, Joyce Lynn-Sze (Hampstead Psychological Associates, 2020)
The outbreak of contagious and pandemic Corona Virus (COVID-19) has made the universities and other educational institutes close down in order to avoid the spread of the virus, in Pakistan. To avoid any interruption in the quality education provision, the universities have adopted technology with the objective to provide uninterrupted educational services to their students. But the technology services are not considered much advanced due to which the student satisfaction cannot be ensured. The main objective of the current study was to explore and investigate the impact of ICT orientation aspects i.e. advantage, ease of use, compatibility and perception on the brand image of universities in Pakistan in the mediating impact of student satisfaction. For this purpose, data were collected from 367 students from various universities of Pakistan through an online questionnaire. The results of the study indicated that ICT orientation has significant impact on student satisfaction as well as university brand image. Similarly the impact of student satisfaction on brand image of university is also significant. Moreover, the mediating impact of student satisfaction is also found as significant on the relationship between ICT orientation and university brand image. Universities may find this study useful to improve their technology factor to ensure student satisfaction and thus the brand image of university.